Servant leadership, employee engagement, employee trust and employee performance in an oil and gas company - Renu, Vahmanithy (2019)
Global challenges associated with the downfall of crude oil price, caused several consequences at organizational human resources level in the form of retrenchment, downsizing and resource restructuring to cope up with the business volatility. Malaysian oil companies are not exempted from such business consequences. In this context, a study was conducted in upstream business units of PETRONAS Sdn Bhd, Oil and Gas Company, where more organizational restructuring was witnessed, to examine the effect of servant leadership on employee trust, employee engagement and employee performance. In order to explore the relationship, this research posed five research questions and seven hypotheses, between the independent variable servant leadership, and dependent variables employee trust, employee engagement and employee performance. Following deductive approach, a cross sectional descriptive study design was applied. Arriving at a sample size of 399 employees, the study followed two sampling techniques, stratified disproportionate sampling and purposive sampling. Structural equation modelling analysis was done with SmartPLS 3.0 structural equation. The findings clearly indicated that servant leadership positively influenced employee trust, employee engagement and employee performance. The findings also indicated that employee trust and employee engagement partially mediates the effect of servant leadership on employee performance. The study has extended practical implications to Human Resource department in PETRONAS Sdn Bhd, in their decision whether to adapt servant leadership orientations during business volatile situations, in order to establish better employee trust, employee engagement and employee performance. The study also extended better knowledge implication by incorporating recent reviews of literatures and facilitating advancement of knowledge. The study provided better insights into the role of servant leadership for better organizational performance.